Weaving in creativity. (2nd December 2021) - Rodgers, Anne
Abstract : Creativity is an important means of encouraging children to experiment and explore the world around them. As children learn through their senses, creative play can help them to achieve and develop physically, emotionally, socially, and intellectually, promoting skills to increase their self-confidence and self-esteem.